The panorama between COVID-19 pandemic and Artificial Intelligence (AI): Can it be the catalyst for Society 5.0? (International Journal of Scientific Research and Management (IJSRM), 2020)
Purpose: During the COVID-19 pandemic, a new age digital era has emerged; Artificial Intelligence (AI) could be instrumental in keeping this new virus within reasonable limits. AI also has the potential to transform communities into super smart Society 5.0. So, the main target of the study is to analyze AI-focused Society 5.0 configuration through the lens of the present emergency. Design/Methodology/Approach: A systematic analysis of literature has been executed to discuss the AI-focused Society 5.0 configuration triggered by pandemic, in which over 300 publications are read and reviewed by the authors. The reliability and validity of literature analysis have also been established. Findings: The analysis confirms that the COVID-19 emergency can be one of the most important drivers, influencing transformation to Society 5.0 through the implementation of AI. This pandemic sets the perfect platform for global adoption of AI-based Society 5.0 to obtain more ethical human and technology collaboration. Research limitation: Prior empirical attempts are subsequently required to inquiry about the proposed conceptualization from different perspectives. Practical implications: The findings will act as a realistic roadmap for applying AI technologies to Society 5.0 outline by the incorporation of open source technologies, supportive regulations, and modern business models. Potential approaches emerging from this research are useful to community managers or large corporations partnering with local agencies to increase the opportunities for the long-term success of smart city projects. Social implications: The outcomes of the study will help to solve social and ecological issues aligned with SDGs. It will also create an innovative platform to utilize the working abilities of older segments of society. Originality/Value: This article is the first to discuss AI-focused Society 5.0 configuration to harness the hidden potential of the COVID-19 pandemic.